2023
DOI: 10.14218/jcth.2023.00029
|View full text |Cite
|
Sign up to set email alerts
|

Portal Hypertension in Nonalcoholic Fatty Liver Disease: Challenges and Paradigms

Abstract: Portal hypertension in cirrhosis is defined as an increase in the portal pressure gradient (PPG) between the portal and hepatic veins and is traditionally estimated by the hepatic venous pressure gradient (HVPG), which is the difference in pressure between the free-floating and wedged positions of a balloon catheter in the hepatic vein. By convention, HVPG≥10 mmHg indicates clinically significant portal hypertension, which is associated with adverse clinical outcomes. Nonalcoholic fatty liver disease (NAFLD) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 132 publications
0
1
0
1
Order By: Relevance
“…Interestingly, in vivo experiments yielded opposite results, with ANO1 expression significantly downregulated in the portal vein of rats with PHT 32 . Notably, elevated portal pressure is the main feature of PHT, 94,95 and these findings provide new ideas for the development of PHT. In addition, a recent study showed that in PVSMCs in a model of cirrhotic PHT, angiotensin II (ANGII) reduced vascular tone and contraction by downregulating the expression of ANO1, 96 but the underlying mechanism is unclear and requires further investigation.…”
Section: Physiological Role Of Ano1 In the Livermentioning
confidence: 96%
“…Interestingly, in vivo experiments yielded opposite results, with ANO1 expression significantly downregulated in the portal vein of rats with PHT 32 . Notably, elevated portal pressure is the main feature of PHT, 94,95 and these findings provide new ideas for the development of PHT. In addition, a recent study showed that in PVSMCs in a model of cirrhotic PHT, angiotensin II (ANGII) reduced vascular tone and contraction by downregulating the expression of ANO1, 96 but the underlying mechanism is unclear and requires further investigation.…”
Section: Physiological Role Of Ano1 In the Livermentioning
confidence: 96%
“…Прогрессирование МАСБП в ряде случаев осложняется развитием портальной гипертензии [37]. В этот период заболевания для контроля над уровнем артериального давления пациентов целесообразно использовать гипотензивные препараты, оказывающие влияние как на системную, так и портальную гипертензию.…”
Section: эффекты сердечно-сосудистых препаратов на патогенез и течени...unclassified